HUBUNGAN TINGKAT PENDIDIKAN DAN TINGKAT PENGETAHUAN DENGAN UPAYA PENCEGAHAN DEMAM BERDARAH DENGUE PADA MASYARAKAT DUKUH KARANGANYAR BUGEL POLOKARTO KARANGANYAR - Budi Herminto; Wiwin Winarni; Yosan Misoni (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Background : based on survey reported by Public Health Center at Polokarto on 2015,the incidence of DHF was increased accounted for 21.43% including people inKaranganyar. Early interview conducted on June 2015 revealed that there were 4 peoplewho suffered from DHF. The observation showed that the sanitation of the environmentwas much dirty. There were a lot of cans which used as mosquito nests. Some people inthat region reported that they have not yet to do prevention against DHF effectively.The purpose of this study was to analyze the correlation between the education level andlevel of knowledge about DHF of people towards the efforts of DHF preventions.Methods : this research used analytic with correlation design. The total populationinvolved in this research were 150 people of Karanganyar region. Sampling technik usedwas total sampling. Data was collected by using questionnaire and observing thebehaviour of the people to collect data of prevention efforts. The data was analyzed usinglogistic regression aided by SPSS serial 16.Results of this study : 1) The majority people of Karanganyar had high level of knowledgeaccount for 96%. 2)The majority people had high level of education account for 65,33%.3) The majority people in Karanganyar had performed less effective of the efforts of DHFpreventions (76%). 4) Level of knowledge (OR=1,611) has stronger correlation than levelof education (OR=0,034) towards the efforts of DHF prevention.Conclusion : that education level dan knowledge level have significant correlation towardthe efforts of DHF prevention.Keywords: level of knowledge, level of education, the efforts of DHF preventions